Optimizing the Professional Role Playing Method to Foster Responsibility and Self Confidence in the Pancasila Education Course for Third Graders at SD Muhammadiyah 2 Kauman Surakarta - Fatma Wulandari; Arief Cahyo Utomo (Journal of Educational Sciences, 2026)
Character education plays a crucial role in shaping students’ attitudes and behaviors starting from elementary school. One of the character traits that needs to be developed is responsibility and self-confidence in learning activities. This study aims to analyze the application of the professional role-playing method in Pancasila Education lessons and its impact on enhancing the responsibility and self-confidence of third-grade students at SD Muhammadiyah 2 Kauman Surakarta. This study employs a qualitative approach using a case study design. The research subjects consisted of Pancasila Education teachers and third-grade students selected through purposive sampling. Data collection techniques included observation, semi structured interviews, and documentation. Data validity was tested through source triangulation and technique triangulation, while data analysis was conducted through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the professional role-playing method is effective in enhancing students’ sense of responsibility, as evidenced by their ability to complete tasks on time, fulfill their learning obligations, adhere to classroom rules, and correct mistakes. Additionally, this method boosts students’ self confidence, demonstrated through their willingness to present in front of the class, express their opinions, and engage in learning activities. However, its implementation still faces challenges such as variations in students’ self-confidence levels and limited class time.